Application of 5-Ethoxymethylfurfural (EMF) for the Production of Cyclopentenones - Bredihhin, Aleksei; Luiga, Sirvo; Vares, Lauri (Synthesis, 2016)
We describe a method for the conversion of 5-ethoxymethylfurfural (EMF) into substituted cyclopentenones in a stereoselective manner through application of the Piancatelli rearrangement. The strategy allows the utilization of biomass-derived C6-carbohydrates for the production of cyclopentenones, making them a possible platform chemical for the sustainable chemical industry.
Keywords: cyclopentenone; 5-ethoxymethylfurfural; 5-hydroxymethylfurfural; Piancatelli rearrangement; biomass valorization